2015
DOI: 10.5194/essd-7-415-2015
|View full text |Cite
|
Sign up to set email alerts
|

In situ measurement of the biogeochemical properties of Southern Ocean mesoscale eddies in the Southwest Indian Ocean, April 2014

Abstract: Abstract. Several open-ocean mesoscale features -a "young" warm-core (anti-cyclonic) eddy at 52 • S, an "older" warm-core eddy at 57.5 • S and an adjacent cold-core (cyclonic) eddy at 56 • S -were surveyed during a R/V S.A. Agulhas II cruise in April 2014. The main aim of the survey was to obtain hydrographical and biogeochemical profile data for contrasting open-ocean eddies in the Southern Ocean, which will be suitable for comparative study and modelling of their heat, salt and nutrient characteristics, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In addition to SCMs in the vicinity of the Polar front (Kopczynska et al, 2001;Parslow et al, 2001;Armand et al, 2008a;Westwood et al, 2011;Tripathy et al, 2015;Rembauville et al, 2016a), ex situ measurements have found summer SCMs around the continental slopes of Antarctica and Southern Ocean islands (Garibotti et al, 2003;Holm-Hansen and Hewes, 2004;Demidov et al, 2007;Armand et al, 2008a;Whitehouse et al, 2008;Erickson et al, 2016), around eddies (Clementson et al, 1998;Daly et al, 2001) and in the Seasonal Ice Zone (Mikaelyan and Belyaeva, 1995;Bathmann et al, 1997;Cailliau et al, 1997;Wright and van den Enden, 2000;Gomi et al, 2007;de Villiers et al, 2015). During summer, a recurrent and notable absence of SCMs has only been reported in the permanently open ocean zone of Antarctic waters (Cailliau et al, 1997;Gomi et al, 2007;Rigual-Hernández et al, 2015a,b) and the Sub-Antarctic zone south of Australia (Figure 4; Clementson et al, 1998;Parslow et al, 2001;Westwood et al, 2011).…”
Section: Reported Occurrencesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to SCMs in the vicinity of the Polar front (Kopczynska et al, 2001;Parslow et al, 2001;Armand et al, 2008a;Westwood et al, 2011;Tripathy et al, 2015;Rembauville et al, 2016a), ex situ measurements have found summer SCMs around the continental slopes of Antarctica and Southern Ocean islands (Garibotti et al, 2003;Holm-Hansen and Hewes, 2004;Demidov et al, 2007;Armand et al, 2008a;Whitehouse et al, 2008;Erickson et al, 2016), around eddies (Clementson et al, 1998;Daly et al, 2001) and in the Seasonal Ice Zone (Mikaelyan and Belyaeva, 1995;Bathmann et al, 1997;Cailliau et al, 1997;Wright and van den Enden, 2000;Gomi et al, 2007;de Villiers et al, 2015). During summer, a recurrent and notable absence of SCMs has only been reported in the permanently open ocean zone of Antarctic waters (Cailliau et al, 1997;Gomi et al, 2007;Rigual-Hernández et al, 2015a,b) and the Sub-Antarctic zone south of Australia (Figure 4; Clementson et al, 1998;Parslow et al, 2001;Westwood et al, 2011).…”
Section: Reported Occurrencesmentioning
confidence: 99%
“…Particularly intense eddy activity occurs where fronts interact with shallow bathymetry (Bryden and Heath, 1985). A small number of SCMs have been attributed to eddies spinning off the Subtropical front, the Sub-Antarctic front and the Antarctic Divergence (Clementson et al, 1998;Wright and van den Enden, 2000;Daly et al, 2001;Westwood et al, 2011;de Villiers et al, 2015). To date, eddies are speculated to facilitate Southern Ocean SCMs by two mechanisms; (1) nutrient-light co-limitation within warm-core eddies from the Subtropical front and (2) increased growth at the pycnocline cold-core eddies from the Sub-Antarctic Front, likely due to the injection of nutrients (Figures 5D,E).…”
Section: Eddiesmentioning
confidence: 99%
“…flow in a growing eddy is contrary to that of a decaying eddy (de Villiers et al, 2015;Sun et al, 2019).…”
Section: Simulation Of the Dynamic Structure Of The Cf Dipolementioning
confidence: 90%